Cannabidiol-Enriched Extract Reduced the Cognitive Impairment but Not the Epileptic Seizures in a Lafora Disease Animal Model - Aso, Ester (2020)
Introduction: Lafora disease (LD) is a rare form of progressive infantile epilepsy in which rapid neurological deterioration occurs as the disease advances, leading the patients to a vegetative state and then death, usually within the first decade of disease onset. Based on the capacity of the endogenous cannabinoid system (ECS) to modulate several cellular processes commonly altered in many neurodegenerative processes, as well as the antiepileptic properties of certain natural cannabinoids, the aim of this study was to evaluate the role of the ECS in LD progression. Materials and Methods: We tested whether a natural cannabis extract highly enriched in cannabidiol (CBD) might be effective in curbing the pathological phenotype of malin knockout (KO) mice as an animal model of LD. Results: Our results reveal for the first time that alterations in the ECS occur during the evolution of LD, mainly at the level of CB1, CB2, and G protein-coupled receptor 55 (GPR55) receptor expression, and that a CBD-enriched extract (CBDext) is able to reduce the cognitive impairment exhibited by malin KO mice. However, in contrast to what has previously been reported for other kinds of refractory epilepsy in childhood, the CBD-enriched extract does not reduce the severity of the epileptic seizures induced in this animal model of LD. Conclusions: In summary, this study reveals that the ECS might play a role in LD and that a CBD-enriched extract partially reduces the dementia-like phenotype, but not the increased vulnerability to epileptic seizures, exhibited by an animal model of such a life-threatening disease.